Preparation method and application of carbon-doped porous boron nitride catalyst for acetylene hydrochlorination reaction

By preparing carbon-doped porous boron nitride catalysts, the existing catalysts have problems of mercury emission pollution, high cost and unstable activity, and achieve efficient, low-cost and environmentally friendly acetylene hydrochlorination reaction effect.

CN119608201APending Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311177905.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing acetylene hydrochlorination reaction catalysts have problems such as mercury emission pollution, high cost, and unstable activity. The intrinsic activity of mercury-free catalysts is poor, making it difficult to meet the needs of industrial applications.

Method used

The catalyst is prepared by mixing the boron source, nitrogen source and carbon source through drying and calcining steps, with a high specific surface area, a porous structure and an adjustable conductivity.

Benefits of technology

It has achieved improvements in catalytic performance, high conversion rate, high selectivity, good stability, low cost, completely free of mercury, suitable for industrial applications, and can carry out acetylene hydrochlorination reaction at a lower reaction temperature, saving energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608201A_ABST
    Figure CN119608201A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carbon-doped boron nitride catalyst for acetylene hydrochlorination. The method comprises the following steps: 1) mixing: heating in an oil bath, and dissolving a boron source, a nitrogen source and a carbon source in a mixed solvent of ethanol and water; 2) drying: drying the solution obtained in the step 1) to obtain a precursor; and 3) calcining: calcining the precursor obtained in the step 2) in an inert atmosphere to obtain the carbon-doped boron nitride catalyst. The prepared catalyst has the characteristics of ultrahigh specific surface area, rich porous structure and defect sites, controllable conductivity and the like, and can be applied to the process of efficiently preparing vinyl chloride through acetylene hydrochlorination. The preparation method is simple, the cost is low, the performance is excellent, the industrialization difficulty is small, the process repeatability is good, a mercury catalyst in an existing calcium carbide process is expected to be replaced, the problem of mercury emission pollution is solved, and a new technical route is provided for mercury replacement of the catalyst in the acetylene hydrochlorination process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing vinyl chloride by hydrochlorination of acetylene, and particularly relates to a preparation method and application of a carbon-doped porous boron nitride catalyst for acetylene hydrochlorination reaction. Background Art

[0002] Vinyl chloride (VCM) was first discovered in 1835 and was industrially produced by the German Griesheim Electronics Company in the 1930s by adding acetylene and hydrogen chloride. It was mainly used in the production of polymer polyvinyl chloride (PVC) resin. PVC has many applications in production and life, such as building materials, industrial products, daily necessities, bottle materials, floor tiles, foam materials, artificial leather, wires and cables, packaging films, floor leather, pipes, sealing materials, fibers, etc. Therefore, its monomer VCM has become one of the most widely produced and used plastic monomers in the world.

[0003] The production process of polyvinyl chloride plastic (PVC) is the polymerization of vinyl chloride monomer (VCM). The production of vinyl chloride monomer can be obtained through the ethylene method, acetylene method and ethane method. Due to the basic national conditions of poor oil and abundant coal, the existing industrial process in China is mainly the acetylene method, in which acetylene and hydrogen chloride undergo electrophilic addition in the presence of a catalyst. In industry, the catalyst used in the acetylene method of vinyl chloride production is prepared by loading mercuric chloride on activated carbon with a high specific surface area (8000-1500m 2 / g, where the mercury loading is about 10wt%. Mercury chloride catalyst (HgCl2 / AC) has high reaction activity and selectivity, as well as good reaction stability, but its use also has many problems. The main problem is that the loss of the active component Hg of the catalyst leads to obvious catalyst deactivation, while also bringing huge environmental and health threats.

[0004] In the recent development of mercury-free catalysts, gold catalysts have shown excellent comprehensive performance, but they also bring the problem of inevitable high costs. Other precious metals and non-precious metals generally show poor performance in acetylene hydrochlorination reactions and have little application prospects. For non-metallic catalysts, they have good activity and low cost, providing a path for mercury-free production of acetylene hydrochlorination.

[0005] In recent years, researchers have tried to improve the catalytic performance of non-metallic catalysts by doping carbon materials with heteroatoms such as boron, nitrogen, and phosphorus, introducing functional groups and constructing defects, and loading ionic liquids. However, no catalyst can simultaneously obtain good intrinsic activity and stability to meet the needs of industrial applications.

[0006] Porous boron nitride is one of the better known non-metallic catalysts, but its intrinsic activity is poor. Therefore, the introduction of new active sites by doping is expected to further optimize the catalytic ability of boron nitride catalysts in acetylene hydrochlorination. Summary of the invention

[0007] In view of the above problems, the present invention provides a preparation method and application of a carbon-doped porous boron nitride catalyst for acetylene hydrochlorination reaction. The catalyst prepared by the present invention has the advantages of adjustable conductivity, ultra-high specific surface area, rich porous structure and defect sites, and the catalytic performance has the advantages of high conversion rate, high selectivity and good stability.

[0008] In order to achieve the above object, the technical solution of the present invention is as follows:

[0009] In one aspect, the present invention provides a method for preparing a carbon-doped boron nitride catalyst for acetylene hydrochlorination reaction, the method comprising the following steps:

[0010] 1) Mixing: heating in an oil bath, dissolving the boron source, nitrogen source and carbon source in a mixed solvent of ethanol and water;

[0011] 2) Drying: drying the solution obtained in step 1) to obtain a precursor;

[0012] 3) Calcination: Calcinate the precursor obtained in step 2) under an inert atmosphere to obtain the carbon-doped boron nitride catalyst.

[0013] In the above technical solution, further, in step 1), the boron source includes one or two of boric acid and boron oxide;

[0014] The nitrogen source includes one or more of urea, dicyandiamide, melamine, biuret, dimethylguanidine and various amino acids;

[0015] The carbon source includes one or more of glucose, sucrose, polyethylene glycol, ammonium citrate, carbon-containing biomass, starch, and resin.

[0016] In the above technical solution, further, in step 1), the temperature of the oil bath is 60-90°C.

[0017] In the above technical solution, further, in step 1), in the mixed solvent of ethanol and water, the volume ratio of ethanol to water is 1:1-1:2.

[0018] In the above technical solution, further, in step 2), the drying temperature is 120-150°C.

[0019] In the above technical solution, further, in step 3), the inert atmosphere is at least one of nitrogen, helium, argon, krypton, and xenon; the calcination temperature is 800-1100° C., and the calcination time is 6-18 hours.

[0020] Another aspect of the present invention provides a carbon-doped boron nitride catalyst prepared by the above preparation method, wherein the carbon-doped boron nitride catalyst has a boron content of 30-45wt%, a nitrogen content of 30-45wt%, and a carbon content of 15-35wt%.

[0021] The present invention also provides an application of the carbon-doped boron nitride catalyst in acetylene hydrochlorination.

[0022] In the above technical scheme, further, the dried and dehydrated hydrogen chloride and acetylene raw gas are introduced into a gas-solid phase catalytic reactor carrying a carbon-doped boron nitride catalyst for reaction, the volume ratio of hydrogen chloride to acetylene is 1.4:1.0-0.6:1.0, the reaction temperature is 140-280°C, and the reaction space velocity is 30-300h -1 , the reaction pressure is normal pressure.

[0023] In the above technical solution, further, the reaction temperature is 140-180°C.

[0024] The beneficial effects of the present invention are:

[0025] (1) The catalyst prepared by the method provided by the present invention has a low preparation cost compared to expensive gold-based catalysts and is more suitable for the current market demand; and the preparation steps are simple, requiring only the mixing of the precursors through a liquid phase reaction and then further drying and calcining to prepare the catalyst; the prepared carbon-doped boron nitride catalyst has a high specific surface area and a controllable carbon content.

[0026] (2) The catalyst prepared by the method provided by the present invention is completely mercury-free, thereby solving the defects of existing industrial low-mercury activated carbon catalysts such as mercury emission pollution and catalyst deactivation due to accidental cessation of hydrogen chloride gas, showing good application prospects;

[0027] (3) The catalyst prepared by the method provided by the present invention does not require pre-activation treatment with hydrogen chloride gas during application, and the application process is more efficient and simple.

[0028] (4) The catalyst prepared by the method provided by the present invention has a unique porous structure, which makes it have great application prospects. In the process of acetylene hydrochlorination, the lower reaction temperature can save a lot of energy, making it have broad industrial application prospects.

[0029] (5) The present invention reduces the band gap of the catalyst and accelerates the flow of carriers by introducing carbon, thereby increasing the conductivity of the catalyst and further improving the intrinsic performance of the catalyst.

[0030] (6) The catalyst prepared by the method provided by the present invention requires a lower temperature when used in the acetylene hydrochlorination process, thereby having a higher intrinsic activity. If the intrinsic activity is too poor, the addition reaction between acetylene and hydrogen chloride cannot be carried out in a timely manner, and the adsorbed acetylene will polymerize, which will become carbon deposits and cause deactivation. However, when the intrinsic activity is improved, the adsorbed acetylene can react with hydrogen chloride in a timely manner, will not polymerize itself, will not be deactivated by carbon deposits, and thus improve the stability of the catalyst (>500h). In addition, the required temperature is lower, which saves more energy costs.

[0031] (7) The catalyst prepared by the method provided by the present invention has a wide temperature application range, has excellent catalytic performance at 140-280°C, has a high conversion rate (>83.5%) and selectivity for vinyl chloride (>97.5%), and has high thermal stability (>500h), and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 XRD spectra of BCN-g#1, BCN-g#2, and BCN-g#3 in Example 1;

[0033] Figure 2 is the XRD spectrum of BCN-MF#1 in Example 2;

[0034] Figure 3 This is the stability test result of BCN-MF#1 in Example 2. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, but the scope of the claims of the present invention is not limited by these embodiments. At the same time, the embodiments only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose.

[0036] The elemental composition of the samples can be determined by X-ray photoelectron spectroscopy.

[0037] The specific surface area of ​​the sample can be tested by nitrogen or argon physical adsorption method.

[0038] The raw materials used in the following examples are all conventional products that can be obtained commercially. The evaluation of the catalysts is carried out in a continuous online gas-solid phase reactor. A typical evaluation process is to weigh 5.00g of catalyst, purge and dry it with argon at 120°C for 0.5h, introduce the reaction gas at 140-280°C to start the reaction, and the product is detected by Agilent gas chromatograph 7890B, equipped with a FID detector, and the chromatographic column used is PLOTQ, which has good separation and detection performance for the gas components involved.

[0039] Example 1

[0040] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid and add it to a mixed solution of 400 ml of water and 200 ml of water. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of ground melamine powder and glucose and gradually add them to the solution with vigorous stirring.

[0041] As stirring proceeds, the dissolved boric acid will quickly react with melamine to precipitate, forming a white flocculent viscous precipitate. In the early stage of formation, its viscosity will make magnetic stirring impossible. If this state is maintained for more than 1 hour, the viscosity of the precipitate will decrease and magnetic stirring will become effective again.

[0042] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0043] There are two points to note in liquid phase synthesis: first, the melamine used needs to be ground into powder in advance. If it is granular melamine, the performance of the sample obtained in the liquid phase synthesis process will be uneven; second, before the final evaporation step, the container needs to be sealed during the stirring process to prevent large-scale dissolution and evaporation during the experiment.

[0044] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18 hours.

[0045] The specific samples and their preparation conditions and parameter performance are shown in Table 1. As a comparative example, BN#1 in the table is a commercially available boron nitride with low carbon content and low specific surface area (manufacturer: Aladdin, model: 1 μm, 98.5%).

[0046] Table 1 Preparation and parameter performance of carbon-doped boron nitride materials

[0047]

[0048] The conductivity results of BCN-g#1, BCN-g#2, BCN-g#3 and BN#1 in Example 1 are shown in Table 2 below, and the results show that through the current synthesis method, the added carbon can effectively improve the conductivity of the material.

[0049] Table 2 Conductivity test results

[0050] sample <![CDATA[Conductivity / S·m -1 > BCN-g#1 0.0149 BCN-g#2 0.0663 BCN-g#3 0.2252 BN#1 0.0002

[0051] Example 2

[0052] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid into a mixed solution of 400 ml of water and 200 ml of water, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of ground melamine powder and polymelamine formaldehyde resin, gradually add them into the above solution, and stir vigorously;

[0053] As stirring proceeds, the dissolved boric acid will quickly react with melamine to precipitate, forming a white flocculent viscous precipitate. In the early stage of formation, its viscosity will make magnetic stirring impossible. If this state is maintained for more than 1 hour, the viscosity of the precipitate will decrease and magnetic stirring will become effective again.

[0054] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0055] There are two points to note in liquid phase synthesis: first, the melamine used needs to be ground into powder in advance. If it is granular melamine, the performance of the sample obtained in the liquid phase synthesis process will be uneven; second, before the final evaporation step, the container needs to be sealed during the stirring process to prevent large-scale dissolution and evaporation during the experiment.

[0056] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0057] The specific samples, their preparation conditions and parameter performance are shown in Table 3.

[0058] Table 3 Preparation and parameter performance of carbon-doped boron nitride materials

[0059]

[0060] Example 3

[0061] (1) Liquid-phase synthesis precursor: Weigh 37.14 g of boric oxide and add it to a mixed solution of 600 ml of water and 200 ml of water. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of ground melamine powder and starch and gradually add them to the above solution with vigorous stirring.

[0062] As stirring proceeds, the dissolved boric acid will quickly react with melamine to precipitate, forming a white flocculent viscous precipitate. In the early stage of formation, its viscosity will make magnetic stirring impossible. If this state is maintained for more than 1 hour, the viscosity of the precipitate will decrease and magnetic stirring will become effective again.

[0063] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0064] There are two points to note in liquid phase synthesis: first, the melamine used needs to be ground into powder in advance. If it is granular melamine, the performance of the sample obtained in the liquid phase synthesis process will be uneven; second, before the final evaporation step, the container needs to be sealed during the stirring process to prevent large-scale dissolution and evaporation during the experiment.

[0065] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0066] The specific samples, their preparation conditions and parameter performance are shown in Table 4.

[0067] Table 4 Preparation and parameter performance of carbon-doped boron nitride materials

[0068]

[0069] Example 4

[0070] (1) Liquid-phase synthesis precursor: Weigh 37.14 g of boric oxide and add it to a mixed solution of 600 ml of water and 200 ml of water. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of ground melamine powder and ammonium citrate and gradually add them to the solution with vigorous stirring.

[0071] As stirring proceeds, the dissolved boric acid will quickly react with melamine to precipitate, forming a white flocculent viscous precipitate. In the early stage of formation, its viscosity will make magnetic stirring impossible. If this state is maintained for more than 1 hour, the viscosity of the precipitate will decrease and magnetic stirring will become effective again.

[0072] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0073] There are two points to note in liquid phase synthesis: first, the melamine used needs to be ground into powder in advance. If it is granular melamine, the performance of the sample obtained in the liquid phase synthesis process will be uneven; second, before the final evaporation step, the container needs to be sealed during the stirring process to prevent a large amount of dissolution and evaporation during the experiment;

[0074] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0075] The specific samples, their preparation conditions and parameter performance are shown in Table 5.

[0076] Table 5 Preparation and parameter performance of carbon-doped boron nitride materials

[0077]

[0078] Example 5

[0079] (1) Liquid-phase synthesis precursor: Weigh 37.14 g of boric acid into a mixed solution of 600 ml of water and 200 ml of water, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of ground melamine powder and sucrose, gradually add them into the solution, and stir vigorously;

[0080] As stirring proceeds, the dissolved boric acid will quickly react with melamine to precipitate, forming a white flocculent viscous precipitate. In the early stage of formation, its viscosity will make magnetic stirring impossible. If this state is maintained for more than 1 hour, the viscosity of the precipitate will decrease and magnetic stirring will become effective again.

[0081] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0082] There are two points to note in liquid phase synthesis: first, the melamine used needs to be ground into powder in advance. If it is granular melamine, the performance of the sample obtained in the liquid phase synthesis process will be uneven; second, before the final evaporation step, the container needs to be sealed during the stirring process to prevent a large amount of dissolution and evaporation during the experiment;

[0083] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0084] The specific samples, their preparation conditions and parameter performance are shown in Table 6.

[0085] Table 6 Preparation and parameter performance of carbon-doped boron nitride materials

[0086]

[0087] Example 6

[0088] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid into a mixed solution of 400 ml of water and 200 ml of water, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of ground urea powder and melamine formaldehyde resin, gradually add them into the above solution, and stir vigorously;

[0089] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0090] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0091] The specific samples, their preparation conditions and parameter performance are shown in Table 7.

[0092] Table 7 Preparation and parameter performance of carbon-doped boron nitride materials

[0093]

[0094]

[0095] Example 7

[0096] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid and add it to a mixed solution of 400 ml of water and 200 ml of water. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of finely ground dicyandiamide powder and melamine formaldehyde resin and gradually add them to the above solution with vigorous stirring.

[0097] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0098] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0099] The specific samples, their preparation conditions and parameter performance are shown in Table 8.

[0100] Table 8 Preparation and parameter performance of carbon-doped boron nitride materials

[0101]

[0102]

[0103] Example 8

[0104] (1) Liquid-phase synthesis precursor: Weigh 37.14 g of boric oxide and add it to a mixed solution of 600 ml of water and 200 ml of water. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of finely ground urea powder and melamine formaldehyde resin and gradually add them to the above solution with vigorous stirring.

[0105] Stir vigorously for 12 h in a sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0106] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0107] The specific samples, their preparation conditions and parameter performance are shown in Table 9.

[0108] Table 9 Preparation and parameter performance of carbon-doped boron nitride materials

[0109]

[0110] Example 9

[0111] (1) Liquid-phase synthesis precursor: Weigh 37.14 g of boric oxide and add it to a mixed solution of 600 ml of water and 200 ml of water. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of finely ground dicyandiamide powder and melamine formaldehyde resin and gradually add them to the above solution with vigorous stirring.

[0112] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0113] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0114] The specific samples, their preparation conditions and parameter performance are shown in Table 10.

[0115] Table 10 Preparation and parameter performance of carbon-doped boron nitride materials

[0116]

[0117] Example 10

[0118] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid into a mixed solution of 400 ml of water and 200 ml of water, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of ground melamine powder and polyethylene glycol, gradually add them into the above solution, and stir vigorously;

[0119] As stirring proceeds, the dissolved boric acid will quickly react with melamine to precipitate, forming a white flocculent viscous precipitate. In the early stage of formation, its viscosity will make magnetic stirring impossible. If this state is maintained for more than 1 hour, the viscosity of the precipitate will decrease and magnetic stirring will become effective again.

[0120] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0121] There are two points to note in liquid phase synthesis: first, the melamine used needs to be ground into powder in advance. If it is granular melamine, the performance of the sample obtained in the liquid phase synthesis process will be uneven; second, before the final evaporation step, the container needs to be sealed during the stirring process to prevent a large amount of dissolution and evaporation during the experiment;

[0122] (2) Calcination: The product obtained above is dried at 120°C in air, granulated into 20-40 mesh, and calcined in an inert atmosphere to obtain a carbon-doped boron nitride material with a high specific surface area. The inert gas is one or more of nitrogen, helium and argon. The calcination temperature is 800-1100°C and the time is 6-18h.

[0123] The specific samples, their preparation conditions and parameter performance are shown in Table 11.

[0124] Table 11 Preparation and parameter performance of carbon-doped boron nitride materials

[0125]

[0126] Application Example 1

[0127] The fixed bed reaction is used as an example, but the catalyst is also suitable for moving bed reactors. The device is equipped with a gas mass flow meter and an online product analysis chromatograph (the tail gas of the reactor is directly connected to the quantitative valve of the chromatograph for periodic real-time sampling and analysis).

[0128] A typical evaluation process is to weigh 5.00g of catalyst, dry it with argon purge at 120℃ for 0.5h, introduce the reaction gas at 140-280℃ to start the reaction, and detect the product by Agilent gas chromatograph 7890B equipped with FID detector. The chromatographic column used is PLOT Q, which has good separation and detection performance for the gas components involved.

[0129] Table 12 lists the specific application of the catalyst and its effect data. The reaction performance can be changed by changing the temperature, air velocity and the molar ratio of C2H2 / HCl in the reaction gas. The conversion rate of acetylene can reach 83.5-99.9%, and the selectivity is 97.5-99.9%. The catalyst of comparative example BN#1 is a commercially available conventional boron nitride. The reaction results of comparative example BN#1 show that the boron nitride material with very low carbon content and specific surface area has poor reaction activity, and the conversion rate is only 8.4%.

[0130] Table 12 Specific application of catalyst and its effect data

[0131]

[0132]

[0133] It can be seen from the above table that different raw materials and different calcination conditions directly affect the carbon content and specific surface area of ​​carbon-doped boron nitride materials, which further affect the conversion rate of acetylene and the selectivity of vinyl chloride.

[0134] Result analysis:

[0135] Figure 1 The XRD spectra of BCN-g#1, BCN-g#2, and BCN-g#3 in Example 1 show that a typical two-dimensional hexagonal graphite structure is obtained by the current synthesis method;

[0136] Figure 2 This is the nitrogen physical adsorption result of BCN-MF#1 in Example 2, indicating that the catalyst has a high specific surface area;

[0137] Figure 3 The stability test results of BCN-MF#2 in Example 2 are shown in Figure 2. Under mild conditions (GHSV = 30 h -1 , 180 ° C, C2H2 / HCl molar ratio = 1.2) tested the stability of the catalyst. Figure 3 It can be seen that the catalyst maintained good stability within 500 h, the conversion rate remained above 95.2%, and the conversion rate was close to 99.8%.

[0138] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-doped boron nitride catalyst for acetylene hydrochlorination, characterized in that: The method comprises the following steps: 1) Mixing: heating in an oil bath, dissolving the boron source, nitrogen source and carbon source in a mixed solvent of ethanol and water; 2) Drying: drying the solution obtained in step 1) to obtain a precursor; 3) Calcination: Calcinate the precursor obtained in step 2) under an inert atmosphere to obtain the carbon-doped boron nitride catalyst.

2. The preparation method according to claim 1, characterized in that: In step 1), the boron source includes one or both of boric acid and boron oxide; The nitrogen source includes one or more of urea, dicyandiamide, melamine, biuret, dimethylguanidine and various amino acids; The carbon source includes one or more of glucose, sucrose, polyethylene glycol, ammonium citrate, carbon-containing biomass, starch, and resin.

3. The preparation method according to claim 1, characterized in that: In step 1), the temperature of the oil bath is between 60 and 90°C.

4. The preparation method according to claim 1, characterized in that: In step 1), in the mixed solvent of ethanol and water, the volume ratio of ethanol to water is 1:1-1:

2.

5. The preparation method according to claim 1, characterized in that: In step 2), the drying temperature is 120-150°C.

6. The catalyst according to claim 1, characterized in that In step 3), the inert atmosphere is at least one of nitrogen, helium, argon, krypton and xenon; the calcination temperature is 800-1100° C., and the calcination time is 6-18 hours.

7. A carbon-doped boron nitride catalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The carbon-doped boron nitride catalyst has a boron content of 30-45 wt%, a nitrogen content of 30-45 wt%, and a carbon content of 15-35 wt%.

8. Use of the carbon-doped boron nitride catalyst according to claim 7 in acetylene hydrochlorination.

9. The use according to claim 8, characterized in that: The dried and dehydrated hydrogen chloride and acetylene raw gas are passed into a gas-solid phase catalytic reactor carrying a carbon-doped boron nitride catalyst for reaction. The volume ratio of hydrogen chloride to acetylene is 1.4:1.0-0.6:1.0, the reaction temperature is 140-280°C, and the reaction space velocity is 30-300h -1 , the reaction pressure is normal pressure.

10. The use according to claim 9, characterized in that: The reaction temperature is 140-180°C.